Uncertainty treatment using paraconsistent logic : introducing paraconsistent artificial neural networks - Silva Filho, João Inácio da (Frontiers in artificial intelligence and applications, 2010)
The aim of the KBIES series is to report on the tremendous range of applications arising out of investigations into intelligent systems, coupled with the latest generic research that makes these applications possible. The series provides a leading resource for researchers, engineers, managers and all others concerned with this area of research, or wanting to know more about it.